40 years of the United nations convention on the law of the sea : assessment and prospects - Kamiński, Tomasz; Karski, Karol (Routledge Research on the Law of the Sea, 2025)
This book discusses contemporary challenges within the law of the sea, a domain of international law extensively codified in United Nations Convention on the Law of the Sea. Given the considerable time elapsed since the convention’s adoption and nearly three decades of its implementation, the book analyses the interplay and influence of its provisions on international customary law, as well as to identify issues arising from its application. The book explores and discusses crucial aspects of the law of the sea, addressing challenges and future perspectives related to UNCLOS provisions, such as the delimitation of maritime areas, maritime security, safety, environmental protection, and the implications of advancing technologies, particularly in the realm of unmanned vessels. Additionally, the book delves into recent maritime legal challenges arising from the conflict in Ukraine and the global impact of the COVID-19 pandemic. The book will be of interest to students and scholars in the field of the law of the sea, international relations and international law.